1996
DOI: 10.1046/j.1365-3148.1996.d01-48.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of clinical transfusion practice by implementation of the privilege of blood prescription and computerized prospective audit of blood requests

Abstract: Guidelines, algorithms and recommendations have been issued in the attempt to ensure appropriateness of transfusion practice, but the results are less than satisfactory, mainly due to the difficulty to turn paper procedures into actual practice. In our hospital we have tried to overcome this difficulty through the implementation of a quality assurance programme which includes giving the privilege of nonurgent blood prescription to a limited number of physicians and a computerized prospective audit of blood req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…It leads to considerable impact on the health care cost, wastage of resources, depriving more needy patients and transmission of infection with unnecessary allergic reaction leading to high mortality and morbidity in patients. 13,14 hence we tried to look into the transfusion practices in patients at a tertiary care hospital by this retrospective study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It leads to considerable impact on the health care cost, wastage of resources, depriving more needy patients and transmission of infection with unnecessary allergic reaction leading to high mortality and morbidity in patients. 13,14 hence we tried to look into the transfusion practices in patients at a tertiary care hospital by this retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies [10][11][12][13][14] it is revealed that for sustained improvement in practice, prospective monitoring must be continued indefinitely. It is difficult due to lack of staff and more time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…For sustained improvement in practice, prospective monitoring must be continued indefinitely. [13,14] Our results showed blood issues and donors are increasing day by day, so the workload. As we have less manpower it is overburdening our present staff.…”
Section: Discussionmentioning
confidence: 75%
“…Due to easy availability, indiscriminate use has been found to be rampant and despite sufficient guidelines and recommendations available, platelets usage remains the most misused component. This inappropriate use of blood and its components have a significant impact on the patients and the hospital staff in the form of health care cost, (10,11) wastage of resources, depriving more needy patients and transmission of infection with unnecessary allergic reaction leading to high mortality and morbidity in the patients. (12) In our study, most of the platelets were utilized for patients of infectious aetiology.…”
Section: Discussionmentioning
confidence: 99%